Religious Radicalism and Pluralism: The Conflict Between Religious People and Relation of Power Industry in Bekasi - Aden Rosadi (International Journal of Nusantara Islam, 2014)
Based on category, this program leads to three social issues. First, public awareness about the significance of the view of life that is more tolerant, open and more pluralis amid development of industrialization. Industrialization that developed in centers of growth (growth poles), which prominently still holdsrural-agrarian values, has given rise to what is called the proletarian farmers. "Proletarisation" was preceded by transition process of the function of farmland into industrial land, thus causing economic activity became more intense and integrated into industrial capitalism. This leads to the occurrence of an identity crisis that led to theopposition attitude in most communities, especially those who associated with the existence of other religions. Second, these changes have an impact on the emergence of community with radical attitude by carrying the religious themes. The construction of houses of worship, which is actually the "House of God" for any religions, considering the dangers may threaten the existence of the community and other faiths. The value system was formed, as a society oppressed became one of the motivators and catalysts for the inception of religious radicalism at the low level community. Third, the Government's policy regarding the construction of a harmony is among believers. This last part is related to the concept of good governance. As an institutional approach, the concept of good governance (good governance) is defined as the interaction between the organizers of the State (Government) and groups in the community. According to the World Bank, there are at least four important dimensions of good governance, i.e. example, effective legal framework, information that is in line with the transparency (accountability or Government) and the availability of well-educated workforce. In this context, the position of District Government of Bekasi becomes one of the institutions, which is responsible for the running of the relationship between the Government, employers or investors, religious figures, and the public as the three interest groups that cannot be separated in developing awareness of pluralism in religious life in the community.